A clinical case of severe aromatic L-amino acid decarboxylase deficiency - O. A. Shidlovskaya; S. B. Artemyeva; E. D. Belousova; Z. K. Gorchkhanova (Нервно-мышечные болезни, 2024)
We present a case of a rare disease, aromatic L-amino acid decarboxylase deficiency (AADCD), with delayed diagnosis even after a pathogenic mutation indicative of AADCD was found. In most cases, AADCD causes marked impairment of motor and psycho- speech development and is accompanied by severe episodes of dystonia – oculogyric crises. The careful attention of neurologists, pediatricians, geneticists, gastroenterologists, and pulmonologists in cases of a complex set of diverse symptoms determines the success of early diagnosis and the earliest possible prescription of modern gene replacement therapy for AADCD.